2016
DOI: 10.1016/j.regsciurbeco.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Education, experience, and urban wage premium

Abstract: Recent studies investigate the urban wage premium associated with education and work experience. We study the effect of work experience and firm tenure across education groups. All education groups benefit more from working in cities, and the extra city wage premium highly educated enjoy over less educated workers is increasing with city work experience. Interestingly, the city wage premium of less educated workers is increasing in firm tenure, while the highly educated gain more by shifting jobs between firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 40 publications
17
54
0
2
Order By: Relevance
“…They state: “workers in big and small cities are not particularly different to start with; it is largely working in cities of different sizes that makes their earnings diverge” (De la Roca & Puga, , p. 109). Carlsen, Rattsø, & Stokke, arrive at similar conclusions based on data on workers in Norway. They find that sorting has some effect, but only for workers with college degrees.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…They state: “workers in big and small cities are not particularly different to start with; it is largely working in cities of different sizes that makes their earnings diverge” (De la Roca & Puga, , p. 109). Carlsen, Rattsø, & Stokke, arrive at similar conclusions based on data on workers in Norway. They find that sorting has some effect, but only for workers with college degrees.…”
Section: Introductionsupporting
confidence: 53%
“…However, these higher wages are offset by higher costs of living, so that, in spatial equilibrium, workers are indifferent between regions (Glaeser, ). These higher wages are often found to take the form of a static (level) effect and a dynamic (growth) effect that accrues over time (Carlsen et al., ; Glaeser & Maré, ; Matano & Naticchioni, ).…”
Section: Understanding Spatial Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…A few scholars argue that selection of initially more productive workers is insignificant in the larger picture, when industrial sector, age and urban experience are taken into account (Baum-Snow & Pavan, 2012;De La Roca & Puga, 2017). The dominating tendency, however, is to observe substantial sorting across central and less central labour markets (we cannot cite all the literature, but see Carlsen, Rattsø, & Stokke, 2016;Combes, Duranton, & Gobillon, 2008;Eeckhout, Pinheiro, & Schmidheiny, 2014;Korpi & Clark, 2019). There is also agreement that rural-urban migrants receive a combination of static and dynamic rewards, usually with larger dynamic premiums for highskilled individuals (Carlsen et al, 2016;Gordon, 2015).…”
Section: Migration and Workmentioning
confidence: 99%
“…Learning continues well after college, and individuals may acquire additional skills in other environments. Carlsen et al () showed that age reflects job tenure from learning within the firm. Education: human capital theory maintains that human capital investment accumulates largely through schooling (Becker ). Schooling contributes to capital by acting as a substitute source of training for skill and apprenticeship.…”
Section: Independent Variables Data and Methodologymentioning
confidence: 99%